Renewable Energy and Electromobility in the EU: Identifying Developmental Synergies Through Cluster Analysis - Monika Ziółko; Monika Hamerska; Maciej Banik; Adrian Machaty (Energies, 2025)
The development of renewable energy in recent years has become an important factor supporting the global shift towards sustainable mobility, particularly in the context of electromobility. This article explores the relationship between the share of renewable energy in the energy mix of the 27 EU countries and the development of electromobility in their area. The objective of the conducted research is to classify the European Union countries into groups that are homogeneous in terms of the level of installed electricity capacity of renewable energy sources, as well as into groups that are homogeneous with respect to the development of electromobility. Cluster analysis was used to achieve this objective. The study will be performed in two main steps. In the first step, clusters of similar European Union countries will be identified in terms of installed electricity capacity and clusters of similar countries in terms of electromobility development. The second step will be based on a comparison of whether the clusters of countries are similar according to the adopted criteria. The cluster analysis method will make it possible to identify groups of countries with similar levels of development in both sectors, which allows the patterns and challenges faced by countries with different development dynamics to be understood.